Recent results from the ANTARES neutrino telescope - Coyle, P.; James, Clancy (2017)
© 2017 by World Scientific Publishing Co. Pte. Ltd. The ANTARES deep sea neutrino telescope has been taking data continuously since its completion in 2008. With its excellent view of the galactic plane and good angular resolution the telescope can constrain the origin of the diffuse astrophysical neutrino flux reported by IceCube. Assuming various spectral indices for the energy spectrum of neutrino emitters, the Southern sky and in particular central regions of our galaxy have been studied searching for point-like objects, for extended regions of emission, and for signal from transient objects selected through multi-messenger observations. For the first time, cascade events are used for these searches. ANTARES has also provided results on searches for hypothetical particles (such as magnetic monopoles and nuclearites in the cosmic radiation), and multi-messenger studies of the sky in combination with various detectors. Of particular note are the searches for dark matter: the limits obtained for the spin-dependent WIMP-nucleon cross section surpassing those of current direct-detection experiments.